SOCIALIZATION TO BECOME ENTREPRENEURS WITH DIGITALIZATION IN THE TEENAGERS OF AL-QAHHAR MOSQUE - Thezar Fiqih Hidayat Hasibuan; Sucitra Dewi; Ahmad Azmi (RADJA PUBLIKA, 2023)
In line with the times, technological advancements are happening more quickly in the digital age. Technology-related tools are not hard to come by. Sophisticated technology is used in almost all education, social, cultural, sports, economic, and political activities to help carry out each activity and solve a problem. The development of communication technology has affected the opinions of many individuals on a wide range of topics, including parenting. In the past, parents used to permit their kids to play classic games with other kids outside the house. But these days, parents are more likely to use digital devices as a gaming medium for their kids. Thereafter, a lot of parents are vying with one another to grant their kids access to and integrate digital technology into their lives..